Transformasi Lembaga Pendidikan Islam melalui Model Bisnis Syariah: Kerangka Strategis Enam Pilar Berbasis Maqashid Syariah: Transforming Islamic Educational Institutions through Sharia Business Models: A Six-Pillar Strategic Framework Based on Maqashid Sharia - Nia Rahmawati Ansari; Ade Nurpriatna; Benny Wahyudi (Risalah Kharisma, 2026)
This study aims to formulate a strategic framework for integrating Islamic business models into the management of Islamic educational institutions to achieve independence, sustainability, and institutional identity reinforcement. Using a Systematic Literature Review (SLR) method following the PRISMA protocol, this research analyzed 25 relevant articles published between 2020 and 2026. The findings reveal that the integration of Islamic business models is holistic, encompassing spiritual, professional, and social dimensions. Key strategies identified include Sharia-based income diversification through business units and cloud accounting for financial management; transformational and Islamic leadership for human resource development; the development of superior programs based on local excellence and Islamic values; and accountable, transparent governance. The study formulates a comprehensive six-pillar strategic framework: Sharia-based income diversification, digital financial governance, value-based human resource development, program innovation, institutional branding, and Maqashid Sharia-based evaluation. This framework offers a novel, integrated model for Islamic education management, bridging the gap between modern managerial practices and Islamic ethical principles. The study's implications provide a practical guide for institutional transformation and a theoretical foundation for future empirical research to test the framework's effectiveness in diverse educational contexts.